A national survey on the teaching provision of undergraduate geriatric medicine in Malaysia - Sallehuddin, Hakimah; Tan, Maw Pin; Blundell, Adrian; Gordon, Adam; Masud, Tahir (Taylor and Francis, 2021)
Malaysia is becoming an aging nation, with 32 medical schools providing 5,000 graduates every year. The extent these graduates have been trained in core concepts in geriatric medicine remains unclear. This work aims to describe the current state of teaching provision on aging and geriatric medicine to the medical undergraduates in Malaysia. A survey was developed by geriatric medicine experts from the Malaysian Society of Geriatric Medicine (MSGM) to review the teaching provision based on the recommended MSGM Undergraduate Geriatric Medicine Curriculum and was sent to all medical schools across the country. The response rate was 50% (16 out of 32 medical schools). Among 16 medical schools, 10 (62.5%) delivered the learning outcomes as part of an integrated curriculum, and five via a mixed geriatric and integrated curriculum at varying degrees of completeness, ranging from 19% to 94%. One particular medical school did not deliver any of the core topics as part of its undergraduate curriculum. It has been identified that the strongest barrier to delivery was lack of expertise, followed by the fact that the topics were not included in the current curriculum. Improvement in teaching provision should be implemented through a concerted effort to adopt a geriatric medical curriculum nationwide, while future research should aim at the interventions taken to address the barriers in its provision.